Development of Flipbook-Based E-Module Teaching Materials to Enhance Independence and Learning Outcomes of High School Students - Pardede, Erni Rugun Maria; Ruslan, Dede; Arwansyah, Arwansyah (Universitas Pendidikan Mandalika, 2025)
This study aims to develop a flipbook-based e-module as an innovative teaching material to enhance students’ independence and learning outcomes in economics at SMA Kalam Kudus Medan. This research employs the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation) involving 31 tenth-grade students as research subject this research. Data collection was conducted through interviews, questionners, and tests, analysed used descriptive statistics and SPSS statistical tests. The validation results indicate that the developed e-module received scoresof 91.67% (high feasible) form subject matter experts, 86.84% (feasible) form media experts, and 79.46% (feasible) from instructional design experts. These findings suggest that the flipbook-based e-module is effective in improving both students’ learning independence and academic performance. Therefore, this teaching material is recommedence for implementation in learning to support the transformation of digital-based education.